Fitogeografia da região do Jarau - Quaraí/RS - Alves, Fabiano da Silva (2012)
Despite its reputation in southern Brazilian culture, the region of Jarau stills few known on the scientific point of view, raving contradictory opinions also about its geomorphology. Regarding to the regional flora, there is a remarkable diversity compared to the rest of the Campanha‟s Plateau, a fact that can be explained by different environments due to relief variations, the rock substratum, and differences on soils and water availability, in favor of habitat differentiation and a correspondent high number of endemic, rare or endangered plant species. The study was conducted in a polygon of 135,16 km2, bordered on the north by Garupá stream, on the south by Quaraí-Mirim stream, and to east and west by imaginary lines corresponding to the longitudes of 56º 28' 39" E and 56º 35' 26" W. Two hundred and seventy six plant species were found in this area, from 62 botanical families, including 64 endemic, rare and/or endangered species. Six types of natural vegetation were recognized in the region, based on physiognomic, floristic and phytoecological parameters: volcanic hill fields, sandstone hill fields, rupestrian fields, riparian forests, isolated group of trees in the midst of open fields, and Inhanduvá Park. Phytogeograpic maps and photos of distinct plants were provided to each recognized type of vegetation. The regional phytogeography recommends include all the studied area in the Uruguayense district of the Pampean Province (sensu Cabrera & Willink), despite the large floristic contribution from the adjoining Chaco, Espinal and Paranense provinces. At last, it is recommended the adoption of decisions toward the protection of the valuable natural patrimony of Jarau region.